Islamic Political Party and Multiculturalism: Hymne and Mars, Non-Moslem and Minority Communities in Partai Keadilan Sejahtera - Aep Susanto; Tina Kartika (Universitas Medan Area, 2022)
Partai Keadilan Sejahtera (PKS) is an Islamic party with a strong Islamic ideology with a large number of cadres and voters (constituents) and is very influential in building multiculturalism in Indonesia. This study is to describe the view of the multiculturalism of Partai Keadilan Sejahtera (PKS) through party policies, and non-Muslim and minority community cooperation. The method used in this study is qualitative research using literature studies sources in the form of books, websites, articles, and newspapers. PKS changed hymns and marches to instill and demonstrate multiculturalism. PKS involves and supports non-Muslims to become party administrators, and candidates for legislative and executive members. PKS also cooperates with minority communities to maintain the integrity, brotherhood, unity, and integrity of the nation. PKS as an Islamic political party makes Pancasila and Bhinneka Tunggal Ika the main values in maintaining multiculturalism in Indonesia.